Cost-effectiveness analysis of telephone cognitive–behaviour therapy for adolescents with obsessive–compulsive disorder - Tie, Hiong; Krebs, Georgina; Lang, Katie; Shearer, James; Turner, Cynthia; Mataix-Cols, David; Lovell, Karina; Heyman, Isobel; Byford, Sarah (BJPsych open, 2019)
Telephone cognitive-behaviour therapy (TCBT) may be a cost-effective method for improving access to evidence-based treatment for obsessive-compulsive disorder (OCD) in young people.AimsEconomic evaluation of TCBT compared with face-to-face CBT for OCD in young people. Randomised non-inferiority trial comparing TCBT with face-to-face CBT for 72 young people (aged 11 to 18) with a diagnosis of OCD. Cost-effectiveness at 12-month follow-up was explored in terms of the primary clinical outcome (Children's Yale-Brown Obsessive-Compulsive Scale, CY-BOCS) and quality-adjusted life-years (QALYs) (trial registration: ISRCTN27070832). Total health and social care costs were higher for face-to-face CBT (mean total cost £2965, s.d. = £1548) than TCBT (mean total cost £2475, s.d. = £1024) but this difference was non-significant (P = 0.118). There were no significant between-group differences in QALYs or the CY-BOCS and there was strong evidence to support the clinical non-inferiority of TCBT. Cost-effectiveness analysis suggests a 74% probability that face-to-face CBT is cost-effective compared with TCBT in terms of QALYs, but the result was less clear in terms of CY-BOCS, with TCBT being the preferred option at low levels of willingness to pay and the probability of either intervention being cost-effective at higher levels of willingness to pay being around 50%. Although cost-effectiveness of TCBT was sensitive to the outcome measure used, TCBT should be considered a clinically non-inferior alternative when access to standard clinic-based CBT is limited, or when patient preference is expressed.Declaration of interestD.M.-C. reports research grants from the Swedish Research Council (Vetenskapsrådet), the Swedish Research Council for Health, working life and welfare (Forte), the US National Institute of Mental Health (NIMH), the UK National Institute of Health Research (NIHR), as well as royalties from Wolters Kluwer Health and Elsevier, all unrelated to the submitted work.